PENDAMPINGAN OTOMATISASI TATA PERSURATAN DIGITAL DI MIS DARUL IHSANIAH ROKAN HULU - Ahmad Ansori; Salfen Hasri; Umar Faruq; Rini Setyaningsih; Eli Sabrifha; Arrum Intan Sari (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Correspondence administration is an essential component in the governance of educational institutions. However, the manual processes still employed by most schools, including MIS Darul Ihsaniah Rokan Hulu, often lead to various obstacles such as delays in archiving, recording errors, and difficulties in data retrieval. To address these challenges, innovation through the digital automation of correspondence management is required. This community service program aimed to provide assistance in implementing digital correspondence automation at MIS Darul Ihsaniah. The activity was carried out using the Participatory Action Research (PAR) approach, consisting of several stages: preparation, training and workshops, implementation and technical assistance, and evaluation. The mentoring activities resulted in a significant improvement in participants’ ability to manage correspondence digitally. The head of the madrasah, administrative staff, and teachers were able to understand the basic concepts of digital correspondence management and apply the use of official email as a medium for communication and official letter delivery. Participants also became proficient in managing documents using Google Drive with a structured folder system and clear access rights. Moreover, they were capable of creating standardized digital letter templates and implementing an automatic letter numbering system through spreadsheets to ensure proper archiving. The tangible impacts of this activity include increased efficiency in the archiving and distribution processes, enhanced administrative professionalism, and the development of a work culture that is more adaptive to information technology within the madrasah environment.